POSITIVE POLITENESS STRATEGIES OF MAJOR CHARACTER’S UTTERANCES IN THE FILM OZ THE GREAT AND POWERFUL - Servitia, Radellah Meilinda (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2017)
Abstract: The objectives of this research were to find out the positive politeness strategy and factors influencing in the major characters? utterances. To conduct this research, the researcher used the descriptive method. To analyze the data, the researcher classified fifteen positive politeness strategies and factors influencing the use of positive politeness strategy in the utterances. The result of the study shows that there were 12 positive politeness strategies in the major characters? utterances. Then, Three strategies were not found in the utterances. Namely Joke; Give (or ask for) reasons; Assume or assert reciprocity. The influencing factors found in the film there were 15 payoffs, 16 social distances, 5 the sizes of imposition and 2 relative powers. The utterances of four major characters that indicate positive politeness strategies. They were: Oz, Theodora, Evanora, and Finley.